2012
DOI: 10.7600/jpfsm.1.491
|View full text |Cite
|
Sign up to set email alerts
|

Status of physical activity in the Japanese population

Abstract: Physical activity surveillance at a population level is important. The National Health and Nutrition Survey of Japan has been carried out annually, and two kinds of assessments for physical activity are included in the survey: total step counts per day, measured by a pedometer, and questions on exercise habits. From peak values seen in 1998 -2000, time trends display a decline of age-adjusted mean steps per day, and the average percentage of regular exercisers has increased only in the age group of 50 years ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
3
1
Order By: Relevance
“…People with high SES usually have healthy diets and enough knowledge to maintain good health. In this study, the physical activity was observed at a mean of 12.3 METs-h/day, equal to 86.1 METs-h/week, almost 3.7 times higher than the Japanese reference value of 23 METs-h/week 27 . In addition, this study population has a mean BMI of 23 ± 3.4 kg/m 2 , lower than that of other studies (27.5 ± 4.6 kg/m 2 ) in the UK and (26.8 ± 4.9) in Ireland 5,28 .…”
Section: Discussioncontrasting
confidence: 54%
“…People with high SES usually have healthy diets and enough knowledge to maintain good health. In this study, the physical activity was observed at a mean of 12.3 METs-h/day, equal to 86.1 METs-h/week, almost 3.7 times higher than the Japanese reference value of 23 METs-h/week 27 . In addition, this study population has a mean BMI of 23 ± 3.4 kg/m 2 , lower than that of other studies (27.5 ± 4.6 kg/m 2 ) in the UK and (26.8 ± 4.9) in Ireland 5,28 .…”
Section: Discussioncontrasting
confidence: 54%
“…In the Japan Health and Nutrition Survey, 2010, step counts for women are 7,458 ± 3,829 steps/day for those 15-19 years, 7,104 ± 4,075 steps/day for those 20-29 years, 6,669 ± 3,361 steps/day for those 30-39 years, 6,986 ± 3,414 steps/day for those 40-49 years, 7,184 ± 3,624 steps/day for those 50-59 years, 6,234 ± 3,612 steps/day for those 60-69 years, and 3,872 ± 3,183 steps/day for those over 70 years. For men, they were 7,872 ± 4,545 steps/day for those 15-19 years, 8,322 ± 4,833 steps/day for those 20-29 years, 8,278 ± 4,901 steps/day for those 30-39 years, 7,873 ± 4,576 steps/day for those 40-49 years, 7,684 ± 4,368 steps/day for those 50-59 years, 7,092 ± 4,379 steps/day for those 60-69 years, and 4,890 ± 3,362 steps/day for those over 70 years [19]. In the present study, those in women and men over 70 years and men 50-69 years were slightly [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria used in the present study for the assignment of participants to the inactive pool were particularly restrictive (i.e., MVPA < 3.3 MET-h/d or step-count < 10,000 steps/d). Consequently, participants randomized to the intervention and control groups presented a relatively high level of activity (8244 ± 2002 steps/d vs. 6636 ± 4169 steps/d) on average in the Japanese population [ 30 ]. However, the PA intervention used in the present study showed promising outcomes, even in the least active participants.…”
Section: Discussionmentioning
confidence: 99%